Increased Fat Absorption From Enteral Formula Through an In-line Digestive Cartridge in Patients With Cystic Fibrosis. Issue 1 (July 2017) - Freedman, Steven; Orenstein, David; Black, Philip; Brown, Perry; McCoy, Karen; Stevens, John; Grujic, Danica; Clayton, Russell
ABSTRACT: Objectives: Supplemental enteral nutrition (EN) is used by approximately 12% of people with cystic fibrosis (CF). The objective of this study was to evaluate the safety, tolerability, and fat absorption of a new in-line digestive cartridge (Relizorb) that hydrolyzes fat in enteral formula provided to patients with CF. Methods: Patients with CF receiving EN participated in a multicenter, randomized, double-blind, crossover trial with an open-label safety evaluation period. Plasma omega-3 fatty acid (FA) concentrations were measured and used as markers of fat absorption. Gastrointestinal symptoms were recorded to evaluate safety and tolerability. Information regarding the effect of EN on appetite and breakfast consumption was also collected. Results: Before study entry, participants had received EN for a mean of 6.6 years at a mean volume of approximately 800 mL, yet had a mean body mass index of only 17.5 kg/m 2 and omega-3 FA plasma concentrations were only 60% of levels found in normal healthy subjects. Compared with placebo, cartridge use resulted in a statistically significant 2.8-fold increase in plasma omega-3 FA concentrations. There were no adverse experiences associated with cartridge use, and a decrease in the frequency and severity of most symptoms of malabsorption was observed with cartridge use. Participants reported increased preservation of appetite and breakfast consumption with cartridge use compared with their pre-study regimen. Conclusions: Use of this in-line digestive cartridge was safe and well tolerated, and resulted in significantly increased levels of plasma omega-3 FA used with enteral formula, suggesting an overall increased fat absorption. Abstract : Supplemental Digital Content is available in the text